Early Diagnosis and Surgical Treatment for Necrotizing Fasciitis: A Multicenter Study - Misiakos, Evangelos P.; Bagias, George; Papadopoulos, Iordanis; Danias, Nickolaos; Patapis, Paul; Machairas, Nickolaos; Karatzas, Theodore; Arkadopoulos, Nickolaos; Toutouzas, Konstantinos; Alexakis, Nickolaos; Konstantoulakis, Manousos N.; Zografos, George; et al. (Frontiers in Surgery, 2017)
Background: Necrotizing fasciitis (NF) is a group of relatively rare infections, usually caused by two or more pathogens. It affects the skin and subcutaneous tissues of lower and upper limbs, perineal area (Fournier’s gangrene) and the abdominal wall. Early diagnosis and aggressive surgical management are of high significance for the management of this potentially lethal disease. Methods: We conducted a retrospective study in patients who presented,during the last decade,at four University Surgical Departments in the area of Athens, Greece, with an admission diagnosis of NF. Demographic, clinical and laboratory data were gathered, and the preoperative and surgical treatment, as well as the postoperative treatment was analyzed for these patients. Results: A total of 62 patients were included in the study. The mean age of patients was 63.7 (47 male patients). Advanced age (over 65 years) (P<0.01) and female sex (P=0.04) correlated significantly with mortality. Perineum was the mostly infected site (46.8%), followed by the lower limbs (35.5%), and the upper limbs and the axillary region (8.1%). Diabetes mellitus was the most common co-existing disease (40.3%), followed by hypertension (25.8%) and obesity (17,7%). The most common symptom was local pain and tenderness (90.3%). Septic shock occurred in 8 patients (12.9%), and strongly correlated with mortality (P<0.01). Laboratory data were used to calculate retrospectively the LRINEC score of every patient; 26 patients (41.9%) had LRINEC score under 6, 20 patients (32.3%) had LRINEC score 6-8 and 16 patients (25.8%) had LRINEC score >9. Surgical debridement was performed in all patients (mean no. of repeated debridement 4.8), and in 16 cases (25.8%) the infected limb was amputated. The mean length of hospital stay was 19.7 days, and the overall mortality rate of our series was 17.7%. Conclusions: Diagnosis of NF requires high suspect among clinicians, as its clinical image is non-specific. Laboratory tests can depict the severity of the disease; therefore they must be carefully evaluated. Urgent surgical debridement is the mainstay of treatment in all patients; the need of repetitive surgical debridement is undisputed.